Challenging injustice : the odyssey of a Bangladeshi economist - Sobhan, Rehman; Centre for Policy Dialogue (Bangladesh) (Dhaka : Centre for Policy Dialogue, 2007)
Collected essays of a Bangladeshi economist and public intelectual.
v. 1. Challenging injustice : the odyssey of a Bangladeshi economist -- v. 2. Milestones to Bangladesh -- v. 3. Political economy of malgovernance in Bangladesh.
Includes bibliographical references and index.
Keywords: Bangladesh -- Economic conditions; Bangladesh -- Politics and government; Bangladesh -- Social conditions